(untitled) (The Research of Medical Science Review, 2025)
Background: High Socioeconomic Status empowers female with self-assurance and can contribute to a healthy life, particularly during pregnancy. Women which are living in urban settings are better equipped to manage conditions such as gestational anemia but face distinct stressors for pregnancy-related anxiety. The lower SES & problems related to living in second biggest city of Province Sindh may potentially leading to a greater frequency of anemia & anxiety during pregnancy. Material & Methods: This study was steered at Zoology Department of University of Sindh with alliance to Liaquat University Hospital (LUH), Hyderabad during from the second month of 2024 to the final month of 2024. 362 pregnant females were recruited. Sampling technique applied was to be “Non- probability Purposive”, then recruited study participants initially interviewed for residence, SES and asked “Hamilton Anxiety Rating Scale-A” to elucidate PSA. Lastly, Hb levels were checked via “automated analyzer”. Results: Pregnancy Specific Anxiety and Gestational Anemia was vastly rampant particularly in urban 75% and 74% respectively. Participants from lower socioeconomic status had steep prevalence of both PSA and GA 40% and 43 % respectively. However, PSA was also higher 40% in middle SES population. P value <0.05 was estimated and predicted to be just significant to suggestive of linkage of anxiety and anemia during pregnancy with urbanization and poverty.